Increasing Awareness of the Risks of Waste Cooking Oil (WCO) to Health and the Environment through Educational Training for the Community in Desa Sumber Rejo, Banyuasin - Normah; Yulianti, Dwi Hawa; Sya'baniah, Nyimas Febrika; Adhiyanti, Nurmalina; Fazira, Yulin; Handani, Rika (Jurnal Abdimas Mandiri, 2025)
The increasing consumption of cooking oil has led to a significant rise in waste cooking oil (WCO) production, posing serious health and environmental risks. Improper disposal of WCO contributes to water and soil pollution, while its repeated use in cooking has been linked to various health issues, including cardiovascular diseases and cancer. This community service programme aimed to raise awareness among housewives in Desa Sumber Rejo, Banyuasin, regarding the dangers of WCO through educational training. The study employed an interactive discussion approach, beginning with a questionnaire to assess participants' prior knowledge, followed by a socialisation session, and concluding with a post-test evaluation. The results revealed that approximately 80% of participants were unaware of WCO hazards before the training. However, post-training assessments showed a significant improvement in understanding, highlighting the effectiveness of targeted educational interventions. This programme underscores the importance of continuous awareness efforts and the promotion of sustainable WCO management practices, such as its potential repurposing into biodiesel or soap, to mitigate its negative impact on health and the environment.